Education, Special Needs, and Autism in the Baltic States: Policy Mapping in Estonia, Latvia, and Lithuania - van Kessel, Robin; Dijkstra, Wiki; Prasauskiene, Audrone; Villeruša, Anita; Brayne, Carol; Baron-Cohen, Simon; Czabanowska, Katarzyna; Roman-Urrestarazu, Andres (Frontiers in Education, 2020)
The Soviet occupation of the Baltic States followed by joining the United Nations (UN) and European Union make these countries an interesting point of comparison in the development of autism and education policy. This study investigates how policies changed following the transition and how the right and access to education are facilitated for autistic children by performing a path dependence analysis. All Baltic States created new education policies following the transition out of the Soviet era, with their accession to the UN and their appetite to follow internationally available guidance. The right to education for all children in was adopted in all education systems. Education facilities for children with disabilities were implemented in all countries. Afterward, all countries started toward the development of more inclusive systems. Nevertheless, the majority of policies did not specify for autism, yet covered special education needs in general. A development in Latvia should be noted, where various special education needs are outlined in national policy, along with provisions and professional assistance required to address them in mainstream or special classrooms. Ultimately, education policy flourished after the transition. Their development caught up to other European Union countries and they are currently working on implementing inclusive education.